Pernikahan di Bawah Umur dan Relasinya Terhadap Keluarga di Kecamatan Slahung Kabupaten Ponorogo - Agus Munib; Miftahul Huda (Journal of Economics, Law, and Humanities, 2023)
This field research with a qualitative approach through subjective assessment of the opinion of these scholars aims to determine the community's understanding of underage marriage, the reality of family couples who carry out underage marriages, and the household conditions of underage marriage actors in three villages located in Slahung District, Ponorogo Regency. Data collection methods use in-depth interviews, observation, documentation, and analysis with Creswell's theory. The results of the study show that: 1) Public understanding regarding underage marriage is still lacking due to the low level of education; 2) The reality of family couples who, after an underage marriage, do not have a job, still depend on their family (father and mother) for the economy of their new family; 3) The condition of the household of the underage marriage actor is still fine, it will be more clearly seen in the next 3 (three) or 5 (five) years so that it will be known that the condition of the underage married couple's household can run harmoniously according to with the goal of marriage or even end in divorce.